Free Convection Boundary Layer Flow near the Lower Stagnation Point of a Solid Sphere with Convective Boundary Conditions in a Micropolar Fluid - Alkasasbeh, Hamzeh Taha; Mohd Zuki, Salleh; Razman, Mat Tahar; Roslinda, Nazar; Ioan, Pop (2014)

(untitled)
In this paper, the mathematical model for free convection boundary layer flow in a micropolar fluid near the lower stagnation point of a solid sphere with convective boundary conditions, in which the heat is supplied through a bounding surface of finite thickness and finite heat capacity, is considered. The transformed and reduced boundary layer equations in the form of ordinary differential equations are solved numerically using an implicit finite difference scheme known as the Keller-box method. Numerical solutions are obtained for the local wall temperature and the local skin friction coefficient, as well as the velocity, angular velocity and temperature profiles. The features of the flow and heat transfer characteristics for different values of the material or micropolar parameter K, the Prandtl number Prand the conjugate parameter γare analyzed and discussed.